2023
DOI: 10.3390/ijerph20054121
|View full text |Cite
|
Sign up to set email alerts
|

Sense of Belonging, Meaningful Daily Life Participation, and Well-Being: Integrated Investigation

Abstract: The association between well-being, sense of belonging, connectedness to community, and meaningful participation in daily life occupations was theoretically proved and demonstrated in several health conditions or specific age groups. This study aimed to investigate an interplay between well-being, sense of belonging, and connectedness, and meaningful participation in a range of daily life occupations among healthy adults of working age in Israel. Participants (N = 121; age: M = 30.8, SD = 10.1; women: N = 94, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 72 publications
0
3
0
1
Order By: Relevance
“…Existing research has suggested that CYP fare better when they feel a “sense of belonging” ( Gottfried, 2014 ; Haim-Litevsky et al, 2023 ; Heyne & Brouwer-Borghuis, 2022 ; Riley et al, 2018, 2020 ). The participant accounts in this study reflected this, showing that when CYP were absent from school, they missed important opportunities for social interaction and friendship.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Existing research has suggested that CYP fare better when they feel a “sense of belonging” ( Gottfried, 2014 ; Haim-Litevsky et al, 2023 ; Heyne & Brouwer-Borghuis, 2022 ; Riley et al, 2018, 2020 ). The participant accounts in this study reflected this, showing that when CYP were absent from school, they missed important opportunities for social interaction and friendship.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, school absence has been argued to negatively affect children and young people’s (CYP) academic skills and attainment ( Allison et al, 2019 ; Department for Education, 2016 ; Hancock et al, 2013 ) and reduce their opportunities for social and emotional growth ( Gottfried, 2014 ; Heyne & Brouwer-Borghuis, 2022 ). Being included in the school community creates a “sense of belonging,” which has positive effects on health and well-being ( Haim-Litevsky et al, 2023 ; Pini et al, 2019 ; Riley et al, 2018 ). If CYP are not in school, and part of the school community, they can miss consequent health and well-being benefits.…”
Section: Introductionmentioning
confidence: 99%
“…This refers to the creation or strengthening of cooperative relationships of trust between individuals in a group who are similar in the way they define themselves and their membership of the group; they therefore share a common identity around which the network is formed to build social cohesion and increase the influence of participants within the wider community (BONDING). The predominant theoretical framework includes four core elements: (a) ‚Membership', addresses feelings of belonging, emotional security and identification; (b) ‚Influence', refers to the ability of members to generate an impact on a community, and vice versa; (c) ‚Integration and need satisfaction' implies that the community is able to provide for the physical and psychological needs of its members, which will reinforce members' commitment to it; (d) ‚Shared emotional connection' arises from identification with a community's shared history through personal investment and interaction with other community members [49][50][51].…”
Section: Psychological Sense Of Community or Sense Of Communitymentioning
confidence: 99%
“…Cultivating a strong sense of local community is important because it can enhance aspects such as mental health, life satisfaction, civic engagement, and community development (Kitchen et al, 2012;Procentese & Gatti, 2022;Rugel, Carpiano, Henderson, & Brauer, 2019;Talò et al, 2014). This cultivation aligns with the fulfilment of the need for belonging, which in turn benefits psychological and social well-being at individual and collective levels (Allen, Kern, Rozek, McInerney, & Slavich, 2021;Haim-Litevsky et al, 2023). Moreover, a sense of local community can serve as a protective factor, buffering the impacts of social, economic, and technological changes (Bowe et al, 2022;Li, Sun, He, & Chan, 2011;Procentese, Capone, Caso, Donizzetti, & Gatti, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The need for belonging is fundamental and universal in human lives (Baumeister, 2012; Baumeister & Leary, 1995; Deci & Ryan, 2000; Haim‐Litevsky, Komemi, & Lipskaya‐Velikovsky, 2023; Maslow, 1954). A sense of community refers to a feeling of belonging, mutual importance among members, and a collective faith in the fulfilment of members' needs through their shared commitment to the group (McMillan & Chavis, 1986).…”
Section: Introductionmentioning
confidence: 99%